(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study aimed to investigate social media addiction among adolescent. Towards this end, 400 school going students were measured. Data were collected by mean ofSocial Media Addiction Scale Student Form by C. Sahin.To analyze the data regression were used.Result revealed that across all models not only highlight the integral role of social media in modern life but also call attention to its potential drawbacks. This necessitates balanced approaches in social media usage, promoting healthier engagement patterns and mitigating adverse effects on mental health and social interactions.